Estimation of changes in cyclic lung strain by electrical impedance tomography: Proof‐of‐concept study. Issue 2 (26th October 2020) - Cornejo, Rodrigo; Iturrieta, Pablo; Olegário, Tayran M. M.; Kajiyama, Carolina; Arellano, Daniel; Guiñez, Dannette; Cerda, María A.; Brito, Roberto; Gajardo, Abraham I. J.; Lazo, Marioli; López, Lorena; Morais, Caio C. A.; et al.
Abstract : Rationale: Cyclic strain may be a determinant of ventilator‐induced lung injury. The standard for strain assessment is the computed tomography (CT), which does not allow continuous monitoring and exposes to radiation. Electrical impedance tomography (EIT) is able to monitor changes in regional lung ventilation. In addition, there is a correlation between mechanical deformation of materials and detectable changes in its electrical impedance, making EIT a potential surrogate for cyclic lung strain measured by CT (StrainCT ). Objectives: To compare the global StrainCT with the change in electrical impedance (Δ Z ). Methods: Acute respiratory distress syndrome patients under mechanical ventilation ( V T 6 mL/kg ideal body weight with positive end‐expiratory pressure 5 [PEEP 5] and best PEEP according to EIT) underwent whole‐lung CT at end‐inspiration and end‐expiration. Biomechanical analysis was used to construct 3D maps and determine StrainCT at different levels of PEEP. CT and EIT acquisitions were performed simultaneously. Multilevel analysis was employed to determine the causal association between StrainCT and Δ Z . Linear regression models were used to predict the change in lung StrainCT between different PEEP levels based on the change in Δ Z . Main results: StrainCT was positively and independently associated with Δ Z at global level ( P < .01). Furthermore, the change in StrainCT (between PEEP 5 and Best PEEP) was accurately predicted by the change in Δ Z ( R 2 0.855, P < .001 at global level) with a high agreement between predicted and measured StrainCT . Conclusions: The change in electrical impedance may provide a noninvasive assessment of global cyclic strain, without radiation at bedside.